2023
DOI: 10.3389/fimmu.2023.1087677
|View full text |Cite
|
Sign up to set email alerts
|

How autophagy, a potential therapeutic target, regulates intestinal inflammation

Abstract: Inflammatory bowel disease (IBD) is a group of disorders that cause chronic inflammation in the intestines, with the primary types including ulcerative colitis and Crohn’s disease. The link between autophagy, a catabolic mechanism in which cells clear protein aggregates and damaged organelles, and intestinal health has been widely studied. Experimental animal studies and human clinical studies have revealed that autophagy is pivotal for intestinal homeostasis maintenance, gut ecology regulation and other aspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 193 publications
(235 reference statements)
0
5
0
Order By: Relevance
“…The implication of autophagy in CD is multifaceted and cell-specific [36,243]. As mentioned before, dysfunctional autophagy in IECs increases the expression of claudin-2 due to reduced lysosomal degradation and the permeability of the intestinal barrier is in-creased [106,244].…”
Section: Role Of Autophagy In CDmentioning
confidence: 85%
“…The implication of autophagy in CD is multifaceted and cell-specific [36,243]. As mentioned before, dysfunctional autophagy in IECs increases the expression of claudin-2 due to reduced lysosomal degradation and the permeability of the intestinal barrier is in-creased [106,244].…”
Section: Role Of Autophagy In CDmentioning
confidence: 85%
“…Beclin1 is an essential autophagy-related protein. Considering that autophagy has been illustrated to be closely associated with the progression of IBD [ 28 , 29 ], whether YTHDC1 participates in regulating autophagy remains to be confirmed. Previous studies have reported that knockdown of YTHDC1 leads to inhibition of autophagy in keratinocytes [ 23 ], and loss of YTHDC1 has an inhibitory effect on mitophagy, which was identified as a biomarker of hypertrophic cardiomyopathy [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, it has been believed that gut inflammation has been only promoted by T helper cells (Th) 1, Th2, Th17 and Tregs, but now we known that inflammation is also induced by other immune cells, cytokines and processes, including macrophages, DCs, tumor necrosis factor (TNF), inflammasome activation, or autophagy ( 113 117 ). Particularly, autophagy deficiency decreases antigen sampling, increases DC maturation, and promotes pro-inflammatory DCs ( 118 ). Atg16l1 autophagy gene deficiency promotes the bacterial translocation of DSS-induced colitis in vivo and regulates autophagy and phagocytosis, which lead to an exacerbation of the intestinal inflammation ( 119 ).…”
Section: Dcs and Inflammatory Bowel Diseasementioning
confidence: 99%